2016
DOI: 10.3390/inorganics4040036
|View full text |Cite
|
Sign up to set email alerts
|

PP-Rotation, P-Inversion and Metathesis in Diphosphines Studied by DFT Calculations: Comments on Some Literature Conflicts

Abstract: The potential energy surface for internal rotation about the phosphorus-phosphorus bond was calculated at the PCM DCM /B3LYP/6-311++G(d,p) computational level for a set of eight symmetrical, unsymmetrical and P-stereogenic diphosphines; H 4 P 2 , Me 4 P 2 , (CF 3 ) 4 P 2 , Ph 4 P 2 , Me 2 P-P(CF 3 ) 2 , Me 2 P-PPh 2 , and the meso-and dl-isomers of Me(CF 3 )P-PMe(CF 3 ) and MePhP-PMePh. Certain trends in the data were elucidated and compared with conflicting data from the literature regarding the relative popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…The mechanism of the diphosphane metathesis shown in Scheme 5 has been previously investigated computationally by Gilheany et al 48 The lowest energy route that they could find involved the ionic intermediate shown in Scheme 5 but the calculated barrier of 36.5 kcal mol −1 was too high to explain the rapidity of the P,P-metathesis that is observed experimentally.…”
Section: Computational Mechanistic Studies Of Diphosphane Metathesismentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of the diphosphane metathesis shown in Scheme 5 has been previously investigated computationally by Gilheany et al 48 The lowest energy route that they could find involved the ionic intermediate shown in Scheme 5 but the calculated barrier of 36.5 kcal mol −1 was too high to explain the rapidity of the P,P-metathesis that is observed experimentally.…”
Section: Computational Mechanistic Studies Of Diphosphane Metathesismentioning
confidence: 99%
“…43,45 Diphosphane metathesis has not been systematically investigated, but an early 31 P NMR study by Harris et al showed that rapid metathesis occurred between Me 2 P-PMe 2 and (F 3 C) 2 P-P(CF 3 ) 2 in CH 2 Cl 2 to form Me 2 P-P(CF 3 ) 2 . 46,47 Gilheany et al 48 have shown that the calculated high energy barrier to P,P-metathesis via a concerted mechanism is not compatible with the observed rapid kinetics for the Me 2 P-P(CF 3 ) 2 system and suggested that pathways involving impurities in the diphosphanes may facilitate the P,P-metathesis process. Grubba et al 26 have succeeded in the preparation of a variety of pure, unsymmetrical diphosphanes containing P-C(alkyl) and P-N bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the method known as quantitative analysis of ligand effects (QALE) relies on experimental data of known ligands and provides the resolution of net donating ability into QALE parameters [18,19]. It should be noted that the pnictogen interactions, as important secondary interactions, of a wide variety of P-donor ligands were studied as well [20,21,22]. The second category uses approaches that focus on the entire transition-metal complex, thereby including the possibility to scrutinize ligand–ligand effects as well [23].…”
Section: Introductionmentioning
confidence: 99%
“…Известно, что производные дифосфина широко используются в качестве катализаторов ряда химических процессов, в частности, сополимеризации этилена и монооксида углерода [1], а сам дифосфин является удобным модельным объектом для исследования барьера внутреннего вращения вокруг связи Р-Р [2]. С другой стороны наличие у нанотрубок широкого набора ценных электрических, магнитных, оптических и механических свойств позволяет активно влиять на физико-химические характеристики объектов, включенных в их полость.…”
unclassified
“…1). Полученные энергетические различия находятся в хорошем соответствии с расчетами в рамках гибридного DFT приближения B3LYP/6-311++G(d,p) [2].…”
unclassified